2019
DOI: 10.1111/mec.15311
|View full text |Cite
|
Sign up to set email alerts
|

Signature of sexual conflict is actually conflict resolved

Abstract: There has been substantial interest of late in using population genetic methods to study sexual conflict, where an allele increases the fitness of one sex at some cost to the other (Mank, 2017). Population genomic scans for sexual conflict offer an important advance given the difficulties of identifying antagonistic alleles from more traditional methods, and could greatly increase our understanding of the extent and loci of sexual conflict. This is particularly true for studies in natural populations, for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Links between genomic parameters and sex-biased gene expression variation have been a somewhat contentious source of evidence of sexual selection, especially antagonistic forms of sexual selection (Kasimatis et al, 2019;Cheng & Kirkpatrick, 2020;Mank et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Links between genomic parameters and sex-biased gene expression variation have been a somewhat contentious source of evidence of sexual selection, especially antagonistic forms of sexual selection (Kasimatis et al, 2019;Cheng & Kirkpatrick, 2020;Mank et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our results do in fact represent a real biological pattern. Mank et al (2020) argue that much of the signal of sex-specific selection that we found results from an artefact discussed by Bissegger et al (2020). That paper reported that in threespine stickleback some autosomal sites have been duplicated onto the Y chromosome.…”
mentioning
confidence: 67%
“…In their News and Views Perspective, Mank, Shu, and Wright (2020) suggest that the main result of our paper (Cheng & Kirkpatrick, 2016) is a bioinformatic artefact. We revealed that there are allele frequency differences (reflected by positive F ST ) between females and males at many sites across the human autosomes.…”
mentioning
confidence: 82%
“…When mapping whole-genome data to a female reference genome, sequence similarity between the male-specific Y chromosome and the autosomes can lead to the perception of allelic differences between males and females. Recent work has shown that that many genes with allelic sex differences are in fact autosomal loci that are either have recent Y duplicates (Bissegger et al 2019; Mank et al 2020) or otherwise display sequence homology to the Y (Kasimatis et al 2020). We can use differences in M:F read depth to identify these genes (Hall et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…When using a female reference genome, reads from genes which have duplicates to the male- specific region of the Y chromosome will map back to original autosomal or X chromosome regions, resulting in elevated M:F coverage ratio (Bissegger et al 2019; Mank et al 2020). For example, if an autosomal gene has one Y duplication, we would expect three copies in males (two autosomal and one Y-linked) and two copies in females, and therefore an average M:F read depth of 1.5.…”
Section: Methodsmentioning
confidence: 99%